Digital Transformation of Islamic Banking and Economic Empowerment of MSMEs - Shaqila Andina; Cut Risya Varlitya; Tajul Aula; Sartika Sri Maulani; Rean afdhali (JIM: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to analyse the impact of digital transformation in Islamic banking on the economic empowerment of micro, small, and medium enterprises (MSMEs) in Banda Aceh City. A quantitative approach was used, employing a survey method involving 35 business actors in the trade, culinary, and service sectors who utilise digital services such as BSI Mobile, Bank Aceh Mobile, and QRIS Syariah. Data was collected through questionnaires and analysed using descriptive statistics and simple linear regression with the help of SPSS. The results show that the digital transformation of Islamic banking has a positive and significant effect on increasing efficiency, business independence, and access to financing based on Islamic principles. Digital services are considered capable of accelerating transactions, increasing transparency, and expanding business networks, although limited digital literacy remains an obstacle. This study concludes that the digitisation of Islamic banking not only promotes efficiency but also serves as a strategic instrument in realising inclusive and sustainable economic growth for MSME players. .